1999
DOI: 10.1002/(sici)1097-4636(199911)47:2<176::aid-jbm7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of the stimulation of bone formation by highly bioactive apatite- and wollastonite-containing glass-ceramic: Released calcium ions promote osteogenic differentiation in osteoblastic ROS17/2.8 cells

Abstract: We analyzed the mechanisms of the efficient bone formation on the osteoconductive surface of apatite- and wollastonite-containing glass-ceramic (AW) by using an in vitro system. AW releases Ca ions and bonds to bone via a submicron-thick hydroxycarbonate apatite (HCA) layer. AW disks were conditioned with simulated body fluid (SBF) to grow HCA layers, and the amount of released Ca ion was regulated by modulating the conditioning time from 24 to 240 h. Surface-transformed AW disks increased alkaline phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 33 publications
(26 reference statements)
3
36
0
3
Order By: Relevance
“…c-fos is expressed in downstream of signal transduction pathways 46) . Bioactive glass ceramic releases calcium ions and promotes the differentiation of osteoblastic ROS17/2.8 cells in vitro 17) . The present results, however, indicate that reducing the calcium concentration below physiological conditions, induced by EGTA or OCP, raised the ALP activity of ST-2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c-fos is expressed in downstream of signal transduction pathways 46) . Bioactive glass ceramic releases calcium ions and promotes the differentiation of osteoblastic ROS17/2.8 cells in vitro 17) . The present results, however, indicate that reducing the calcium concentration below physiological conditions, induced by EGTA or OCP, raised the ALP activity of ST-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The driving force of this change stems from the decrease of the degree of supersaturation in the solution to form HA, which is the most thermodynamically stable salt at physiological conditions 15) . Previous reports have shown that bioactive glass ceramic releases Ca 2+ and promotes the differentiation of osteoblastic cells in vitro 17) . Pi are also known to play multiple roles in maintaining osteoblast-like cells 18) .…”
Section: Introductionmentioning
confidence: 92%
“…Maxian et al 31 reported that alkaline phosphatase could be enhanced by hydroxyapatite with low crystallinity compared with high crystallinity in a rat calvarial bone cell culture system, and hydroxyapatite with low crystallinity showed greater calcium release than hydroxyapatite with high crystallinity. On the other hand, Matsuoka et al 32 reported that increased extracellular ionized calcium concentration in the culture medium by release from apatite-containing and wollastonite-containing glass ceramics enhanced alkaline phosphatase activity, and promoted osteogenic differentiation in ROS17/2.8 cells.…”
Section: Discussionmentioning
confidence: 99%
“…HA has a composition and structure analogous to the bone apatite and shows high bioactivity (Suchanek et al, 2002;Landi et al, 2004 ;). Calcium silicate is used in drug delivery and bone tissue regeneration due to its good biocompatibility, bioactivity, and degradability (Matsuoka et al, 1999;Oyane et al, 2003;Cortes et al, 2004;Jain et al, 2005;Kokubo et al, 2005). Recently, the key point of the present research aims to the synthesis of HA (Rudin et al, 2009) and calcium silicate nanostructures by novel methods.…”
Section: Fabrication Of Calcium-based Inorganic Biodegradable Nanomatmentioning
confidence: 99%